An Efficient Perlite/Fe3O4 Magnetic Nanocatalyst for Carbon Dioxide Fixation Under Solvent-free Conditions at Atmospheric Pressure of CO2 - Farshid Eskandari; Mohammad Bayat (شیمی کاربردی روز)
The increasing reliance, on fuels has led to an increase in the levels of carbon dioxide causing concerning outcomes like climate change and global warming. In response to this problem, there is a solution; CO2 fixation. In this study, Fe3O4 became changed with the mineral perlite to create magnetic nanomaterials. Fe3O4/Perlite magnetic nanomaterials had been created the use of a co-precipitation technique. In this research, we have presented Perlite/Fe3O4 magnetic nanocatalyst for the transformation of carbon dioxide and epoxides into cyclic carbonates without using solvents at atmospheric pressure of CO2. The Perlite/Fe3O4 magnetic nanocatalyst and products were examined using analysis methods like FTIR, FE-SEM, VSM, EDAX, XRF, NMR, and TGA analysis. The analysis showed the success development of Fe3O4/Perlite with the favored magnetic nanoparticles on its surface. The catalyst exhibited excellent efficiency in generating cyclic carbonate through the activation of CO2 and epoxide. Among the epoxides,1-Chloro-2,3-epoxypropane completed the best conversion fee of 98%, finishing the system in a fast 4.5 h. This approach offers advantages, including mild reaction conditions, solvent-free, the atmospheric pressure of CO2, high yields, simple workup process, inexpensive catalyst, environmentally friendly, short reaction times, and convenient catalyst removal using an external magnet. The catalyst can be reused multiple times, up to 5 cycles, without a significant decrease in its efficiency.